2021
DOI: 10.3390/s21186272
|View full text |Cite
|
Sign up to set email alerts
|

The Short-Term Performances of Two Independent Gas Modulated Refractometers for Pressure Assessments

Abstract: Refractometry is a powerful technique for pressure assessments that, due to the recent redefinition of the SI system, also offers a new route to realizing the SI unit of pressure, the Pascal. Gas modulation refractometry (GAMOR) is a methodology that has demonstrated an outstanding ability to mitigate the influences of drifts and fluctuations, leading to long-term precision in the 10−7 region. However, its short-term performance, which is of importance for a variety of applications, has not yet been scrutinize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 33 publications
(77 reference statements)
1
16
0
Order By: Relevance
“…This contributes to its uncertainty by 20 parts-permillion, which is on par with the uncertainties of pressure balances used in the circular comparison. Its short-term precision has been shown to be significantly better than its uncertainty, in the 1:10 8 range [4].…”
Section: System Detailsmentioning
confidence: 99%
See 3 more Smart Citations
“…This contributes to its uncertainty by 20 parts-permillion, which is on par with the uncertainties of pressure balances used in the circular comparison. Its short-term precision has been shown to be significantly better than its uncertainty, in the 1:10 8 range [4].…”
Section: System Detailsmentioning
confidence: 99%
“…The refractometry system, denoted the Transportable Optical Pascal (TOP), has previously been described in detail [3], [4]. Besides a brief IMEKO 24 th TC3, 14 th TC5, 6 th TC16 and 5 th TC22 International Conference 11 -13 October 2022, Cavtat-Dubrovnik, Croatia 2 of 7…”
Section: The Transportable Refractometermentioning
confidence: 99%
See 2 more Smart Citations
“…The GAMOR methodology has also, thanks to its mitigation of the influence of various types of disturbances, made it possible to construct transportable systems [15], [16], [17]. A comparison between two GAMOR-based systems has demonstrated that the systems have an extraordinarily high short time precision, in the 10 -8 range [16].…”
Section: Wp1: Pressure Measurements Based Onmentioning
confidence: 99%